The philosophy of nature in the poetry of Ghulam Sarwar Yousuf and William Wordsworth: a comparative ecocritical analysis - Alvi, Amatulhafeez; Ravichandran Vengadasamy,; Amrah Abdul Majid, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper is a comparative ecocritical investigation considering the relationship between man and nature in cross-cultural contexts as reflected in the poetry of two great admirers of nature in England and Malaysia: William Wordsworth and Ghulam Sarwar Yousuf. Both poets have composed poetry that strengthens man’s bonds with nature and inspires environmental consciousness. Their nature poetry has been previously studied from different individual perspectives, but none has approached it comparatively from an ecocritical stylistic viewpoint. This study aims at analyzing selected nature poetry to identify the unique philosophy of nature both poets adopted, highlighting the artistic and aesthetic values their poetry are teeming with. The study demonstrates the cognitive development of the poets’ environmental consciousness through three phases of attitudes towards nature; the physical, the intellectual and the mystical. Using major ecocritical concepts like ecocentrism, symbiotic interrelationship and ecological consciousness, the study adopts a comparative stylistic approach to scrutinize linguistic and literary representation of nature in the selected poems. It identifies the similarities and differences between both poets concluding that despite differences in their times, places, cultures, language and style, there is an affinity between both poets in their treatment towards nature. The present study responds to the enormous need for literary-linguistic investigation of leitmotifs of nature across geographical, cultural, and linguistic contexts as a means of facilitating environmental sensitivity and sensibility.